Geospatial genetics: Integrating genetics into marine protection and spatial planning. Issue 9 (24th June 2021) - Kershaw, Francine; McClintock, Will; Andrews, Kimberly R.; Riet‐Sapriza, Federico G.; Caballero, Susana; Tetley, Michael J.; Notarbartolo di Sciara, Giuseppe; Hoyt, Erich; Goldberg, Grace; Chou, Emily; Kane‐Ritsch, Kelsey; Rosenbaum, Howard C.
Abstract: The protection of evolutionary processes and maintenance of genetic diversity is necessary for the persistence of biodiversity and ecosystem resilience. The importance of genetic diversity has been reflected in a range of marine policy mechanisms, and the genetic 'toolbox' has great potential to support marine protection and marine spatial planning (MSP) at multiple scales. Despite scientific advances in the application of genetics in marine protection and management, systematic integration of genetic information has been generally lacking, primarily due to a knowledge and communication disconnect between geneticists and the marine policy and management community. To meet these outstanding needs, a 'geospatial genetics' approach to spatially map species‐specific genetic data and associated information in a way that can be readily integrated by practitioners into marine protection and MSP decisions was developed. Techniques to derive geospatial genetic data layers, which can be viewed and mapped alongside other kinds of spatial data commonly used by conservation practitioners, hold promise for increasing the accessibility of genetic data to support policy decisions more fully. While applicable to many mobile and sessile taxa, an initial focus was placed on marine mammals, and the approach was developed and refined through a series of international meetings and published papers, as well as the development of interactive, expert‐reviewed case studies hosted on the MSP tool SeaSketch. Outcomes of the work to date are currently serving in the policy arena by informing the identification of Important Marine Mammal Areas, an initiative led by the IUCN Marine Mammal Protected Areas Task Force to apply criteria to identify marine mammal habitats across the world's ocean, seas and relevant inland waters through a standardized process. It has become clear that geospatial genetics has great potential to foster increased collaboration among an intersectional community of geneticists, spatial ecologists, and practitioners. This increased opportunity for dialogue and cooperation will help ensure that evolutionary processes are factored into marine protection and MSP processes, and potentially for freshwater and terrestrial systems.